2021
DOI: 10.3389/fnut.2021.701588
|View full text |Cite
|
Sign up to set email alerts
|

Sour Taste SNP KCNJ2-rs236514 and Differences in Nutrient Intakes and Metabolic Health Markers in the Elderly

Abstract: Single nucleotide polymorphisms (SNPs) in taste receptors influence dietary choices that contribute to health and quality of life. Individual differences in sour taste perception and preference have been linked to heritable genetics, yet the impact of sour taste receptor SNPs on sour taste is under-researched, and studies on sour taste SNP associations to diet and health are lacking. Therefore, this study explored the relationships between the sour taste SNP KCNJ2-rs236514 and estimated macronutrient, vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Additionally, bitter taste receptors have also been revealed of the function to evoke airway smooth muscle relaxation via localized calcium flux, predicting the potential role in counteracting asthmatic bronchoconstriction ( Deshpande et al., 2010 ). Recent studies have also found that older carriers of variant rs236514 (A) of the KCNJ2 gene, which is located in Type III sour-sensing taste cells and affects sour perception thresholds, have a higher preference for acid and lower energy intake, along with an increased risk of mild-to-severe cognitive impairment ( Chamoun et al., 2018b ; Ferraris et al., 2021a ; Ferraris et al., 2021b ).…”
Section: Regulation Of Taste Receptors On Oral Microbiota-host Intera...mentioning
confidence: 99%
“…Additionally, bitter taste receptors have also been revealed of the function to evoke airway smooth muscle relaxation via localized calcium flux, predicting the potential role in counteracting asthmatic bronchoconstriction ( Deshpande et al., 2010 ). Recent studies have also found that older carriers of variant rs236514 (A) of the KCNJ2 gene, which is located in Type III sour-sensing taste cells and affects sour perception thresholds, have a higher preference for acid and lower energy intake, along with an increased risk of mild-to-severe cognitive impairment ( Chamoun et al., 2018b ; Ferraris et al., 2021a ; Ferraris et al., 2021b ).…”
Section: Regulation Of Taste Receptors On Oral Microbiota-host Intera...mentioning
confidence: 99%